Development and validation of Triticum phytobiological method as an alternative procedure for investigating in vivo acute toxicity on mice - Emil Ştefănescu; Aurelia N. Cristea; Cornel Chiriță; Octavian Olaru; Adriana Anghel; Mihaela Dinu (Journal of Mind and Medical Sciences, 2017)
The goal of this study was to validate an alternative method for determining in vivo acute toxicity using vegetal material instead of laboratory animals, starting from the phytobiological method known also as the Triticum technique. We set out to demonstrate that vegetal cells have similar sensitivity to some toxic agents as animal cells, in which case a statistical correlation could be established. A series of new compounds synthesized by the Romanian National Institute for Chemical Pharmaceutical Research and Development as potential β3 adrenergic receptors agonists were tested for their acute toxicity using classic animal exposure models, before investigating possible anti-diabetic and anti-obesity effects. We then determined whether similar conclusions might be reached exposing vegetal material to the same agents. We successfully demonstrated that plants are affected in a very similar way as animals when exposed to some potentially toxic agents, providing new possibilities for ending unethical animal experiments.